Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China - Pang, Yin; Su, Cheng-Yuan; Zhu, Dao-Hong (Zootaxa, 2018)
A new gall wasp species, Dryocosmus liui Pang, Su et Zhu n. sp., is described from Hunan Province, China. The new species forms integral galls on branches of Castanopsis tibetana Hance. The results of morphological comparison, pair-wise genetic distance of mtDNA COI, and phylogenetic analysis based on COI gene sequences did not support treating Chilaspis and Dryocosmus as separate genera. Our results also provided new evidence supporting the notion that the Nearctic Dryocosmus species may represent a lineage distinct from the Old World species of the genus.